Mediterranean diet and knee osteoarthritis outcomes: A longitudinal cohort study. Issue 6 (December 2019) - Veronese, Nicola; Koyanagi, Ai; Stubbs, Brendon; Cooper, Cyrus; Guglielmi, Giuseppe; Rizzoli, Renè; Punzi, Leonardo; Rogoli, Domenico; Caruso, Maria Gabriella; Rotolo, Ornella; Notarnicola, Maria; Al-Daghri, Nasser; et al.
Summary: Objectives: Mediterranean diet has several beneficial effects on health, but data regarding the association between Mediterranean diet and knee osteoarthritis (OA) are limited mainly to cross-sectional studies. We investigated whether higher Mediterranean diet adherence is prospectively associated with lower risk of radiographic OA (ROA), radiographic symptomatic knee OA (SxOA) and pain worsening in North American people at high risk or having knee OA. Methods: Adherence to the Mediterranean diet was evaluated using a validated Mediterranean diet score (aMED), categorized in five categories (Q1 to Q5, higher values reflecting higher adherence to Mediterranean diet). Knee OA outcomes included incident (1) ROA, (2) SxOA, as the new onset of a combination of a painful knee and ROA, (3) knee pain worsening, i.e. a Western Ontario and McMaster Universities Osteoarthritis Index difference between baseline and each annual exam of ≥14%. Results: 4330 subjects (mean age: 61.1 years; 58.0% females) were included. Based on a multivariable Poisson regression analysis, during a mean follow-up period of 4 years, participants who were more highly adherent to a Mediterranean diet (Q5) reported lower risk of pain worsening (relative risk, RR = 0.96; 95% CI: 0.91–0.999) compared to those in Q1. In 2994 people free from SxOA at baseline, higher adherence to a Mediterranean diet was associated with a lower risk for SxOA during follow-up by 9% (Q5 vs. Q1; RR = 0.91; 95% CI: 0.82–0.998). No significant associations emerged between aMED and incident ROA. Conclusion: Higher adherence to Mediterranean diet is associated with a lower risk of pain worsening and symptomatic forms of knee OA.